Food safety knowledge, attitudes, and practices of Lettuce market vendors in selected public wet markets in Upland Cavite, Philippines - Quitan, Ruth M.; Prof. Francisco, Maria Leonora Lotis dL.; Dognidon, Kenneth Andrew R. (Quezon City University of the Philippines Diliman, 2023)
Lettuce is a vital vegetable crop for the agriculture-dependent economy of Cavite. However, recent food safety concerns have been linked to the consumption of minimally processed vegetables, highlighting the need to reassess food safety practices in the lettuce supply chain. This study examined the food safety knowledge, attitude, and practices (KAP) of lettuce vendors in public wet markets in upland Cavite, Philippines. The survey included 53 lettuce market vendors and focused on the six key areas outlined in the Code of Sanitation of the Philippines, namely (1) quality of food, (2) protection of food, (3) hand hygiene, (4) sanitary condition of utensils and food contact surfaces, (5) solid waste management, and (6) disease control. Interventions were determined using the Food and Agriculture Organization threshold. The results showed that 73.6% of the food vendors were female, with 30.8% of them being college graduates. Despite 52.8% of them having more than 10 years of vending experience, 69.8% of the vendors had not received any food safety training. Additionally, 69.8% of the vendors did not have an updated health certificate from the local government. Disease control scored the lowest for both food safety knowledge and attitude, with only 7.5% of vendors being able to identify critical health conditions, and 62.3% responding that they found it difficult to not work despite feeling unwell. However, despite these low scores, 75.5% of the vendors responded that they would not work if they had certain health conditions. Although the results showed high frequency scores in practices, this did not necessarily translate into food safety knowledge or attitudes. The study highlights the need for practical and mandatory basic food safety training to improve the current policies surrounding markets and vendors, particularly in the six focus areas identified in the study.
Thesis
Includes bibliographical references (pages 73- 92)
Keywords: Hydroponics -- Philippines; Lettuce -- Phillipines; Markets -- Philippines; Food -- Safety measures -- Philippines; Food handling -- Philippines